Extramedullary myeloma in ectopic parathyroid adenoma: a case report - Nagehan Ozdemir Barisik; Ozge Hande Gunes; Guven Yilmaz; Sevinc Hallac Keser; Aylin Ege Gul; Cem Cahit Barisik (Journal of the Pakistan Medical Association, 2020)
Abstract Extramedullary myeloma, a subgroup of multiple myeloma, is a rare condition characterised by extra-skeletal infiltration of clonal plasma cells. Although parathyroid adenoma’s co-morbidity with multiple myeloma is common, extramedullary myeloma, an ectopic parathyroid adenoma has not been reported in the literature. This is the first study in literature that presents extramedullary myeloma that infiltrated ectopic parathyroid adenoma in the mediastinum after multiple myeloma treatment. In its course of relapse, the extramedullary myeloma created mass effect and no laboratory findings were present due to its non-secretory nature. Keywords: myeloma, metastasis, adenoma, parathyroid Continuous....